Caring Behaviour Mahasiswa Keperawatan Selama Stase Praktik Klinik Maternitas dan Anak - Fakhriatul Falah; Fatmawati Mohamad; Citra Devy Napu (Journal Nursing Care Jurusan Keperawatan Politeknik Kesehatan Gorontalo, 2021)
Background: One of the efforts to increase patient satisfaction is to enhance caring values in delivering nursing services. Caring behavior needs to be instilled in nursing students from an early stage to build the character of nurses with strength integrityObjective: This study aims to obtain a description of the caring behavior of students during clinical practice at the pediatric and maternity ward.Methods: The study used a descriptive study design. The sample is 43 nursing students who are undergoing pediatric and maternity clinical practice. The sampling technique used purposive sampling method.Results: Based on the results of the study, there were 37.8% of students showed caring behavior in the sufficient category, 35.6% in the good category and 26.7% showed less caring behavior.Conclusion: Most of the students still showed caring behavior in the moderate category. Caring behavior in students during the implementation of clinical practice needs to be further improved.